Τhe impact of economic crisis on the regional disparities and the allocation of economic branches in Greek regions - Christofakis, Manolis; Gaki, Eleni; Lagos, Dimitrios (Bulletin of Geography. Socio-economic Series, 2019)
The purpose of this paper is to analyse the changes occurred in regional disparities and sectoral specialization of the Greek regions due to the economic crisis. In this framework, we explore the regional disparities, along with the allocation and specialization of economic sectors in two separate time periods, the pre-crisis period (2000-2007) and the crisis period (2008-2014). The variable used is regional employment in the branches of economic activity. The methods used are Coefficient of Variation, Location Quotients and Shift-Share Analysis. According to the results, we classify the spatial units into categories and we propose means of regional policy. The results show that the disparities increased during the first period and declined in the next period of crisis, without however reaching the levels of 2000. In the first period the dynamic economic sectors are concentrated mainly in the metropolitan region of Attiki and in the insular region of Notio Aigaio, while local advantages are shown in several regions except Attiki. During the period of crisis Attiki and Notio Aigaio have lost their sectoral dynamism, while few regions resist. Regarding the local share effects, the more urbanized regions show negative local shares. The rest of regions exhibit local advantages.